2020
DOI: 10.1101/2020.06.08.141341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence of distinct subpopulations of mechanosensory neurons onto a neural circuit that elicits grooming

Abstract: Diverse subpopulations of mechanosensory neurons detect different mechanical forces and influence behavior. How these subpopulations connect with central circuits to influence behavior remains an important area of study. We previously discovered a neural circuit that elicits grooming of the Drosophila melanogaster antennae that is activated by an antennal mechanosensory chordotonal organ, the Johnston's organ (JO) (Hampel et al., 2015). Here, we describe anatomically and physiologically distinct JO mechanosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The aDNs project to a zone in the VNC where circuitry for generating antennal grooming leg movement patterns is thought to reside ( Berkowitz and Laurent, 1996 ). While this circuit is postsynaptic to the JONs ( Hampel et al, 2020b ; Hampel et al, 2015 ), preliminary connectomic analysis reveals that it is also postsynaptic to BMNs (not shown). Future studies will define the BMN connectivity with the antennal grooming circuit, and other neurons (and circuits) whose activation elicit aimed grooming of different head locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aDNs project to a zone in the VNC where circuitry for generating antennal grooming leg movement patterns is thought to reside ( Berkowitz and Laurent, 1996 ). While this circuit is postsynaptic to the JONs ( Hampel et al, 2020b ; Hampel et al, 2015 ), preliminary connectomic analysis reveals that it is also postsynaptic to BMNs (not shown). Future studies will define the BMN connectivity with the antennal grooming circuit, and other neurons (and circuits) whose activation elicit aimed grooming of different head locations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies showed that optogenetic activation of different sensory and interneuron types elicits grooming of specific head locations, suggesting that they are components of putative parallel circuits ( Cande et al, 2018 ; Guo et al, 2022 ; Hampel et al, 2015 ; Seeds et al, 2014 ; Zhang et al, 2020 ). Third, we identified different neuron types whose activation elicit grooming of the antennae and showed that they are connected to form a neural circuit ( Hampel et al, 2020b ; Hampel et al, 2015 ). The inputs to this circuit are JONs that detect tactile stimulations of the antennae and project to the SEZ where they excite two interneuron types (aBN1 and aBN2) and a descending neuron type (aDN) to elicit grooming.…”
Section: Discussionmentioning
confidence: 99%
“…The aDNs project to a zone in the VNC where circuitry for generating antennal grooming leg movement patterns is thought to reside (Berkowitz and Laurent, 1996). While this circuit is postsynaptic to the JONs (Hampel et al, 2020b, 2015), preliminary connectomic analysis reveals that it is also postsynaptic to BMNs (not shown). Future studies will define the BMN connectivity with the antennal grooming circuit, and other neurons (and circuits) whose activation elicit aimed grooming of different head locations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies showed that optogenetic activation of different sensory and interneuron types elicits grooming of specific head locations, suggesting that they are components of putative parallel circuits (Cande et al, 2018; Guo et al, 2022; Hampel et al, 2015; Seeds et al, 2014; Zhang et al, 2020). Third, we identified different neuron types whose activation elicit grooming of the antennae and showed that they are connected to form a neural circuit (Hampel et al, 2020b, 2015). The inputs to this circuit are JONs that detect tactile stimulations of the antennae and project to the SEZ where they excite two interneuron types (aBN1 and aBN2) and a descending neuron type (aDN) to elicit grooming.…”
Section: Discussionmentioning
confidence: 99%